THE RELATIONSHIP BETWEEN KNOWLEDGE OF BALANCED NUTRITION AND THE NUTRITIONAL STATUS OF ADOLESCENT GIRLS IN SMP NEGERI 6 PEKANBARU - Brilian Dini Ma. Iballa; Sellia Juwita; Indriani Aprilia (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Background: One of the problems that often occurs in teenagers is nutritional problems, this is caused by inappropriate nutritional behavior, such as an imbalance between nutrition and recommended nutritional adequacy. The World Health Organization (WHO) states that adolescents in the 13-15 year age group in the world have nutritional problems, namely 26.9% with short and very short nutritional status. The aim of this research was to determine the relationship between knowledge of balanced nutrition and the nutritional status of adolescent girls at SMP Negeri 6 Pekanbaru. The method used in this research is a quantitative research type with an Observational Analytical research design using a Cross Sectional approach. This research was conducted at SMP Negeri 6 Pekanbaru from 29 May to 30 May 2024. The tools used in this research were questionnaires and leaflets. The population in this study were all class VII students at SMP Negeri 6 Pekanbaru aged 12 to 15 years, namely 197 female students. The sampling technique used probability sampling technique with a simple random sampling method with a sample of 132 female students. Data analysis used univariate and bivariate with the Spearman correlation test. The results of this research showed that the majority of adolescent girls' knowledge at SMP Negeri 6 Pekanbaru was in the sufficient category, namely 82 female students (62.1%), and the majority of nutritional status at SMP Negeri 6 Pekanbaru was in the normal category, namely 59 female students (44.7). . The results of the Spearman correlation test obtained p value = 0.048, namely <0.05. The conclusion of this research is that there is a relationship between knowledge of balanced nutrition and the nutritional status of adolescent girls at SMP Negeri 6 Pekanbaru.